(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
This study aimed to develop science process skills—such as classifying, inferring, and observing—among Grade 3 pupils. To enhance learning in Science 3, particularly in topics related to the sense organs (specifically the skin), the Touch Train was employed as a gamified teaching tool. The study was guided by Sert and Panier’s (2023) Sensory Theory, which emphasizes the vital role of sensory stimulation—especially touch—in effective learning. The theory asserts that engaging the sense of touch activates specific neural pathways, improving the brain’s ability to process and retain information. The researchers adopted a quantitative research approach utilizing a quasi-experimental, one-group pre-test–post-test design to evaluate changes in participants’ performance before and after the intervention. A total of 40 Grade 3 pupils from Urduja Elementary School were selected through purposive sampling. The study employed a researcher-made survey questionnaire, along with pre-test and post-test assessments, as the primary data-gathering instruments. The collected data were analyzed using various statistical tools, including percentage, ranking, weighted mean, and Z-test, to determine the effectiveness of the intervention. The study findings indicated that the respondents demonstrated a solid grasp of science process skills. Classification received a weighted mean of 3.19, interpreted as “Agree,” suggesting it was helpful during content interaction. Inferring followed with a mean of 3.14 (“Agree”), highlighting its effectiveness in helping teachers explain scientific concepts. Observing received the highest mean score of 3.22 (“Agree”), showing its value in evaluating students through performance-based tasks. Additionally, the pre-test and post-test results showed a clear performance improvement. Notably, 23 respondents, or 57.5% of the total sample, scored between 25 and 30 in the post-test, which was interpreted as “Excellent.” The statistical analysis revealed a p-value of < .00001, indicating a significant difference between the pre-test and post-test scores, thereby leading to the rejection of the null hypothesis. The study concludes that Grade 3 pupils successfully developed science process skills—namely, classifying, inferring, and observing—through the use of the Touch Train, which fostered critical thinking and active engagement. The Touch Train proved effective in enhancing classification skills and supporting content interaction. Moreover, the incorporation of gamification encouraged deeper engagement by stimulating curiosity, resulting in a more dynamic, interactive, and meaningful learning experience.